Exploring quantum materials and applications: a review - Rajat Kumar Goyal; Shivam Maharaj; Pawan Kumar; M. Chandrasekhar (Journal of Materials Science: Materials in Engineering)
Abstract Researchers in condensed matter physics are currently exploring new materials for specific use in various applications. The peculiar properties of quantum materials (QMs) have garnered significant attention because they have the potential to serve as building blocks for entirely new technologies in modern science and technology. QMs exhibit emerging phenomena governed by quantum confinement, strong electronic correlations, topology, and symmetry, making them exceptional materials. This review paper provides an overview of these unique properties, different types of QMs, and their applications with the latest case studies, presenting a prospective outlook on QMs in multiple domains.